Eccentric Exercise for Achilles Tendinopathy: A Narrative Review and Clinical Decision-Making Considerations - Jayaseelan, Dhinu J. (J Funct Morphol Kinesiol, 2019)
Background: Achilles tendinopathy is a common health condition encountered in the orthopedic and sports medicine settings. Eccentric exercise is a common intervention in the management of pain and limited function for this patient population, although contemporary evidence suggests additional exercise methods may be effective as well. Study design: Narrative review: Methods: A literature review was performed using the electronic databases Pubmed and PEDRO for articles through February 2019. Randomized clinical trials integrating eccentric exercise, with or without co-interventions, were evaluated. Outcomes related to pain and/or function were considered. A patient case is provided to highlight decision making processes related to clinical prescription of eccentrics for Achilles tendinopathy. Results: After screening titles and abstracts, seven studies were included for full review. Two articles compared eccentric exercise to a control group, four compared eccentrics to the use of modalities, while one used eccentric exercise as part of a multimodal intervention. In each case, eccentric exercise was effective in reducing pain and improving function. In comparison to other forms of exercise or additional interventions, eccentric exercise was frequently not more effective than other options. Discussion: Eccentric exercise has been associated with clinical benefit in improving pain and function for patients with Achilles tendinopathy. Despite the available evidence reporting effectiveness of eccentrics, other options may be equally useful. Appropriate load modification and exercise prescription for patients with Achilles tendinopathy requires systematic clinical reasoning and incorporation of patient values to optimize outcomes.